BEYOND THE PHASE: A CRITICAL REVIEW OF THE MENSTRUAL CYCLE AND FEMALE ATHLETIC PERFORMANCE - Julia Adasiewicz; Katarzyna Kwaterska; Agata Kutyłowska; Karol Kutyłowski; Monika Gajda-Bathelt; Agnieszka Benecka; Kamil Janawa; Michał Tomaszek; Alicja Katarzyna Chojniak; Paweł Jan Kuna (International Journal of Innovative Technologies in Social Science, 2025)
Background: The influence of the menstrual cycle on female athletic performance is a topic of growing interest, yet the scientific literature is characterized by widespread and often contradictory findings. This inconsistency is largely attributed to historical methodological shortcomings, creating a confusing evidence base for athletes, coaches, and practitioners. Aim of the study: This critical review synthesizes the contemporary evidence on the menstrual cycle’s influence on athletic performance, injury risk, and physiological mechanisms. It critically analyzes the factors contributing to the literature’s inconsistency and proposes an evidence-based path forward for research and practice. Materials and Methods: A comprehensive review of contemporary and foundational literature was conducted through a search of the PubMed database. This review synthesized 52 studies, which were thematically organized to analyze the evidence pertaining to objective performance outcomes, athlete perception and symptoms, injury risk profiles, physiological mechanisms, and emerging methodological standards. Conclusions: The evidence suggests the menstrual cycle’s direct impact on performance is likely trivial. However, its influence becomes profound when considering effects on overall health, symptom experience, and recovery physiology. The most critical factor appears to be the presence of a healthy, ovulatory cycle, as performance and physiological markers remain stable in anovulatory athletes. For ovulatory women, the primary influence may not be on maximal capacity but on recovery and a dynamic injury risk profile that shifts throughout the cycle. Therefore, this review concludes that a personalized, athlete-centered approach focused on monitoring cycle health and managing symptoms is a more evidence-based strategy than universal, phase-based training guidelines.